2013
DOI: 10.1177/0954407013503627
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cylinder deactivation on the performance of a diesel engine

Abstract: In this paper, the deactivation of diesel engines used in road vehicles was studied because it changes the progress of combustion, which might be advantageous to the economy of engines. Based on a one-dimensional simulation and an experimental study of a supercharged diesel engine which deactivates half the cylinders at light loads and idle, this paper presents results which show that, when the mean effective pressure of the engine is lower than 3.5 bar, cylinder deactivation decreases the brake specific fuel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 2 publications
1
11
0
Order By: Relevance
“…This fuel consumption improvement was combined with a 40 °C–160 °C increase in exhaust temperatures. Ding et al 8 and Mo et al 11 found similar results for CDA, each demonstrating fuel consumption improvements of approximately 25% at idle conditions with increased exhaust temperatures. While the literature does note some concern that the reduction in airflow with CDA could prove problematic for transient response in diesels, Gosala et al 12 and Joshi et al 9 showed that implementing CDA at and around idle conditions results in no transient response deterioration.…”
Section: Introductionmentioning
confidence: 73%
“…This fuel consumption improvement was combined with a 40 °C–160 °C increase in exhaust temperatures. Ding et al 8 and Mo et al 11 found similar results for CDA, each demonstrating fuel consumption improvements of approximately 25% at idle conditions with increased exhaust temperatures. While the literature does note some concern that the reduction in airflow with CDA could prove problematic for transient response in diesels, Gosala et al 12 and Joshi et al 9 showed that implementing CDA at and around idle conditions results in no transient response deterioration.…”
Section: Introductionmentioning
confidence: 73%
“…Yang demonstrated an improvement of 1-13% in fuel efficiency using Cylinder Cutout operation on an excavator's diesel engine (Yang et al, 2012). At low loads, Mo demonstrated in Mo et al (2013) that Cylinder Cutout has significantly higher pumping losses than CDA. Figure 1A illustrates the speed and load for the engine used in this study as operated over the HDFTP.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study described in [18] revealed significant fuel economy gains at low engine load when switching off two cylinders of a four-cylinder diesel engine. According to [19], cylinder deactivation in diesel engines may result in fuel consumption advantages of up to 17.5% while simultaneously increasing exhaust gas temperature. In [20], an improvement of fuel consumption of 10-30% through cylinder deactivation is reported for a sixcylinder diesel engine.…”
Section: Introductionmentioning
confidence: 99%